ENTERPRISE RISK MANAGEMENT DISCLOSURE AS AN INTERVENING VARIABLE IN THE EFFECT OF GOOD CORPORATE GOVERNANCE IMPLEMENTATION AND FIRM SIZE ON FINANCIAL PERFORMANCE (STUDY ON BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2013 – 2018 - Leventa Moezaque, Dessie; Daito, Apollo (Dinasti International Journal of Economics, Finance & Accounting, 2020)
This study aims to examine the effect of the Implementation of Good Corporate Governance and Firm Size on Financial Performance with Enterprise Risk Management Disclosure as an intervening variable. The analysis technique used in this study is multiple linear regression analysis, with the population of banking companies listed on the Indonesia Stock Exchange during the period 2013 to 2018. From the specified sample criteria there were 39 companies that met the criteria. The results of this study indicate that (1) GCG implementation has no significant effect on ERM Disclosure; (2) Firm Size has a positive and significant effect on ERM Disclosure: (3) The application of GCG has a positive and significant effect on Financial Performance; (4) Firm Size has a positive and significant effect on Financial Performance; (5) ERM disclosure has no significant effect on Financial Performance; (6) ERM disclosure does not mediate between the Implementation of GCG to Financial Performance; (7) The disclosure of ERM does not mediate between Firm Size and Financial Performance.